Management and Control of Variables for the Generation of Biogas from Pig Zungo (2020)
This research focuses on determining the potential of biogas generation for combustion from the Zungo pig manure (manure mixture of the three sizes of the pig in a proportion of 33.33% for each size) located in the department of the Atlantic-Colombia. The properties of the biogas obtained were evaluated with a gas analyzer and a chromatograph, demonstrating that, under controlled temperature conditions, after the bio digestion of Zungo pig manure there is a methane content greater than 50%, which is acceptable demonstrating that this biogas is flammable. It was also established that there is a correlation between pH and methane content in biogas, so it is required to control it in the process.